Features of the delivery and distribution of alkane-naphthene hydrocarbons in the bottom sediments of the Kandalaksha Bay of the White Sea. - Peresypkin, Valery I; Aleksandrov, A V (PANGAEA, 1996)
Data on alkane-naphthene hydrocarbon and organic carbon distributions in the upper layer of bottom sediments from the Kandalaksha Bay of the White Sea are presented. Alkane-naphthene hydrocarbon contents vary from 43.8 to 305.7 µg/g (0.88-60% of organic carbon). Oil pollution of the surface layer of bottom sediments was recognized over a cross-section from the oil station toward the open part of the bay. It is shown that significant amounts of terrigenous and technogenic organic matter are accumulated in fine silty sediments of the deeper parts of the bay and in its inlets. Analysis of alkane composition indicates predominantly terrigenous origin of the major portion of organic matter and evidences high degree of its transformation during accumulation.
Content and composition of hydrocarbons in the upper layer of bottom sediments from the Kandalaksha Bay, White Sea
Keywords: Archive of Ocean Data; ARCOD; Carbon, organic, total; Carbon analyser AN-7529, 7560; Chromatographic; DEPTH, sediment/rock; Extraction; Grab; GRAB; Hydrocarbons; Kandalaksha Bay, White Sea; n-Alkane, sum, assigned to total organic carbon; n-Alkane of hydrocarbons; Organic matter; Per-WhS-49; Per-WhS-BM1; Per-WhS-BM2; Per-WhS-BM3; Per-WhS-MP1; Per-WhS-MP2; Per-WhS-MP3; Per-WhS-MP4; Per-WhS-MP5; Per-WhS-MP6; Per-WhS-MP7; Per-WhS-MP8; Per-WhS-OL; Per-WhS-R1; Per-WhS-R2; Per-WhS-R3; Per-WhS-VG1; Per-WhS-VG2; Per-WhS-VG3; Per-WhS-VG4; Pristane/Phytane ratio; Sediment type; Sum(C11-C22)/sum(C23-C42) n-alkanes; Sum even numbered n-alkanes; Sum n-alkanes C11-C17; Sum n-alkanes C11-C22; Sum n-alkanes C18-C24; Sum n-alkanes C23-C42; Sum n-alkanes C25-C28; Sum n-alkanes C29-C35; Sum odd numbered n-alkanes